Sulfur origin and flux variations in fumarolic fluids of Vulcano Island, Italy - Inguaggiato, Salvatore; Liotta, Marcello; Rouwet, Dmitri; Tassi, Franco; Vita, Fabio; Schiavo, Benedetto; Ono, Shuhei; Keller, Nicole Simone (Frontiers in Earth Science, 2023)
A sharp increase in volatiles, mainly CO2 from the soils of the Levante Bay and crater areas, and SO2 from the plume in 2021, suggest renewed volcanic activity on Vulcano island. This event has encouraged monitoring activities and stimulated new research activities aimed at understanding the recent evolution of the volcanic system. In this study, the chemical and isotopic composition of fumaroles, thermal waters, and soil gases from the main degassing areas of Vulcano Island, with a special focus on Sulfur isotopes, are used to investigate the fluid transfer mechanism inside the volcano. Sulfur is one of the most abundant volatile elements in magmas and in volcanic fluids from La Fossa crater, where it mostly occurs as SO2 and H2S at variable relative concentrations depending on oxygen fugacity and temperature. In addition, we utilize the SO2 monitoring networks installed on Vulcano island that measures the total outgassing of SO2 with the UV-scanning DOAS technique. the SO2 fluxes from the La Fossa crater fumaroles, coupled with the SO2/CO2 and SO2/H2O ratios, were measured to evaluate the total mass of fluids emitted by the shallow plumbing system and its relationship with the status of volcanic activity. Combined with the whole chemical composition of fumaroles analyzed with a discrete, direct sampling of high-temperature fumaroles located on the volcano summit, the output of discharged water vapor, we estimated the total thermal energy dissipated by the crater during the last enhanced degassing activity.